Advancements in Nanostructured Drug Delivery Systems: A Commentary on Multifunctional Approaches for Cancer and Inflammatory Disease Treatment - Varshosaz , Jaleh (Journal of Composites and Compounds, 2023)
Nanostructured drug delivery systems (NDDS) represent a transformative advancement in medical science, offering innovative solutions for the treatment of cancer and inflammatory diseases. These systems utilize nanoscale materials to enhance the efficacy and specificity of drug delivery, allowing for targeted therapy that minimizes side effects. By improving the bioavailability of therapeutic agents, NDDS can significantly increase treatment effectiveness. Furthermore, their ability to navigate biological barriers opens new avenues for overcoming challenges in conventional drug delivery methods.